1973
DOI: 10.1113/expphysiol.1973.sp002231
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intravascular Injections of Veratrine on Laryngeal Resistance to Airflow in Cats

Abstract: Changes in laryngeal resistance to airflow have been measured in cats during spontaneous breathing through the larynx, and while the larynx was isolated in 8itU with constant airflow. Intravenous injections of veratrine resulted in apnoea with a large increase in laryngeal resistance, followed by expiratory increases in laryngeal resistance. These responses were abolished by cutting the vagi in the chest and were absent on injection of veratrine into the left atrium, which established the pulmonary nerves as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1974
1974
1986
1986

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The control of its lumen depends on a complicated system of afferent information integrated in the central nervous system. Some lung reflexes Stransky, Szereda-Przestaszewska & Widdicombe, 1973;Szereda-Przestaszewska & Widdicombe, 1973a), and chemical irritation of the upper airways (Szereda-Przestaszewska & Widdicombe, 1973b) increase expiratory laryngeal resistance to airflow. Initial experiments have shown similar effects on intravascular injections of potassium cyanide to stimulate peripheral chemoreceptors .…”
mentioning
confidence: 99%
“…The control of its lumen depends on a complicated system of afferent information integrated in the central nervous system. Some lung reflexes Stransky, Szereda-Przestaszewska & Widdicombe, 1973;Szereda-Przestaszewska & Widdicombe, 1973a), and chemical irritation of the upper airways (Szereda-Przestaszewska & Widdicombe, 1973b) increase expiratory laryngeal resistance to airflow. Initial experiments have shown similar effects on intravascular injections of potassium cyanide to stimulate peripheral chemoreceptors .…”
mentioning
confidence: 99%
“…This may explain some of the uncertainties in the literature concerning the action of the Hering-Breuer inflation reflex on laryngeal calibre (e.g. Green & Neil, 1955;Eyzaguirre & Taylor, 1963;Szereda-Przestaszewska & Widdicombe, 1973b), since these studies have been based largely on recordings from inspiratory laryngeal motor fibres. Our results with resistance breathing confirm those of Dziewanowska-Kunert (1969) and of Dziewanowska & Szereda-Przestaszewska (1973), who have shown that inspiratory vagal motor fibres, presumably going to the larynx, increase their discharge on addition of a resistance to the tracheal cannula, in rabbits with vagi intact or cut.…”
Section: Discussionmentioning
confidence: 99%